2012
DOI: 10.1007/s00246-012-0579-y
|View full text |Cite
|
Sign up to set email alerts
|

Leftward Displacement of Septum Primum in Hypoplastic Left Heart Syndrome

Abstract: Embryologic development of atrial septum primum antedates formation of the atrioventricular and semilunar valves. Leftward displacement of the superior attachment of septum primum (LDSP) has only been described in hypoplastic left heart syndrome (HLHS). This study reports the frequency of LDSP in HLHS and correlates LDSP with other echocardiographic features of HLHS. Preoperative echocardiograms for 72 consecutive patients with classic HLHS from 1996 to 2002 at Children's Hospital of Wisconsin were reviewed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…8 Absence of the superior limbic band of septum secundum (~95%) in these patients was hypothesised to cause malposition of the septum primum. 7,9 In the series by van Praagh et al, all but three of 36 cases with septum primum malposition defects had confirmed heterotaxy syndrome. 2 A recent study of patients with hypoplastic left heart syndrome showed that 64% of patients had leftward displacement of the septum primum.…”
Section: Discussionmentioning
confidence: 96%
“…8 Absence of the superior limbic band of septum secundum (~95%) in these patients was hypothesised to cause malposition of the septum primum. 7,9 In the series by van Praagh et al, all but three of 36 cases with septum primum malposition defects had confirmed heterotaxy syndrome. 2 A recent study of patients with hypoplastic left heart syndrome showed that 64% of patients had leftward displacement of the septum primum.…”
Section: Discussionmentioning
confidence: 96%
“…A more recent article from Park et al studied the atrial septal morphologies of 71 consecutive patients with HLHS [Park 2013]. The most common morphology seen was LDSP (64%).…”
Section: Discussionmentioning
confidence: 99%
“…The most common type is the ostium secundum (1), accounting for about 50% of cases; 4 however, the variant with leftward anterior deviation of the septum primum (2) seems to be equally common (Fig 1), at least at the severe end of the spectrum. 5 The ostium primum (3) is associated with unbalanced right-dominant atrio-ventricular septal defect. Less frequently, congenitally small or absent atrial septal defect (4) and aneurysm of septum primum (5) have been reported.…”
Section: A Trial Septal Defect Is a Central Issue In Thementioning
confidence: 99%
“…5 The ostium primum (3) is associated with unbalanced right-dominant atrio-ventricular septal defect. Less frequently, congenitally small or absent atrial septal defect (4) and aneurysm of septum primum (5) have been reported.…”
Section: A Trial Septal Defect Is a Central Issue In Thementioning
confidence: 99%
See 1 more Smart Citation